Serum lipid profile and C-Reactive protein as prognostic markers in oral submucous fibrosis - K Jayanthiswari; G V. Murali Gopika Manoharan; S Muthukumar (Wolters Kluwer Medknow Publications, 2022)
Introduction: Oral submucous fibrosis is a chronic, premalignant condition of the oral mucosa, affecting millions of people globally and it is one of the precancerous conditions most prevalent in India. Previously published studies have evaluated the serum lipid profile and C-reactive protein in various potentially malignant disorders and oral squamous cell carcinoma, but to our knowledge, no studies are available comparing the pre- and post-treatment serum lipid profile and C-reactive protein values in oral potentially malignant disorders, so that their real prognostic value can be assessed. Aim: The present study aims to evaluate the serum lipid profile and C-reactive protein as a prognostic marker in Oral Submucous Fibrosis patients. Materials and Methods: A total of 30 clinically diagnosed OSF patients of either gender in the age group of 20 - 50 years were selected. A complete history taking followed by a thorough oral examination was done on all patients. About 5 mL of blood sample was collected before treatment and after 6 weeks of treatment for estimation of serum lipid profile and C-reactive protein Results: The mean values of serum lipid profile were decreased among OSF patients and the difference between pre- and post-treatment was statistically significant. The comparison of the mean values of the pre- and post-treatment CRP level of the study subjects among OSF patients was found to be statistically significant (P = 0.022). Conclusion: Hence, pre- and post-treatment serum lipid profile and CRP levels contribute to being of prognostic value in OSF.